Content analysis of the nature of science on elementary thematic textbooks 2013 curriculum - Irfan Jaenudin; Pratiwi Nur Aisyiah; Rani Suryani; Ari Widodo (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
The 2013 curriculum thematic learning book is used as the primary textbook in thematic learning in elementary schools. This study aims to describe the Nature of Science (NOS) content in the book. This study used a descriptive quantitative research design with the research objects are thematic learning textbooks for 2013 curriculum elementary school students from grades 1-6. Data were collected through observation techniques using a research instrument that contains the analysis of the aspects of the NOS. The data are analyzed through grouping, scoring, determining the validity and reliability, then describing and drawing conclusions. The results showed that the level of content of the NOS in the thematic learning books of the 2013 curriculum elementary school students was 12%, so that it could be categorized as significantly less. These data illustrate that the aspects of the NOS in thematic books already exist but have not been fully presented explicitly, correctly, entirely, and consistently.